Pola Distribusi Petani Tembakau di Kecamatan Bulu Kabupaten Temanggung - Al-hafidz, Zulfikar; Waridin, Waridin; Suciati, Ika (Jurnal AGRISEP, 2023)
Temanggung Regency is one of the areas that distributes the largest tobacco products in Central Java Province. The strategic location on the slopes of a mountain makes tobacco plants suitable to be used as a source of agriculture in the region. The large number of agricultural lands spread across Temanggung Regency provides abundant agricultural products. But in reality, the development of this tobacco farmer business has experienced many problems, such as unstable selling prices, decreased farmer productivity, and changing harvest times. This research study aims to analyze the factors that influence the income of tobacco farmers in Temanggung Regency. This study uses primary data through direct observation and direct interviews with tobacco farmers using questionnaires and secondary data as research support. The results of this study indicate that the marketing of tobacco produced by farmers has several channels such as warehouses, brokers, factories, tengquats, and small traders. Suggestions for further research by adding marketing margin analysis and added value analysis to enrich the research discussion.